Construire une identité professionnelle enseignante dans le paradigme de la complexité : réflexions et questions ouvertes en didactique des langues et des cultures - Mariella Causa; Marine Totozani (Recherches en didactique des langues et des cultures)
This contribution offers some epistemological thoughts about the professional identity of the language teacher in language and cultural didactics. Initially, drawing on various research in language didactics and our own research, we suggest to trace the evolution of the conception of the language teacher's professional identity since the 2000s. This panorama will in turn serve as a basis for highlighting some of the salient elements and new questions raised by the growing complexity of the field of language didactics, in order to lead to a conception of the language teacher’s professional identity in permanent transformation, through four movements that seem to well illustrate the current changes and evolutions of this identity.